EIGRP Routing Performance Analysis with Simulated Shortest Path Selection Using Dijkstra Algorithm - Teresa Martuah Purba; Angela Steffani Sitanggang; Suriaty Padang; Anastasya Jesica Sidauruk; Elsahday Tambunan, (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2025)
This study aims to analyze the performance of the Enhanced Interior Gateway Routing Protocol (EIGRP) in selecting the best path and compare it with the shortest path generated by the Dijkstra algorithm through network simulation. EIGRP is a dynamic routing protocol that uses composite metrics such as bandwidth and delay, whereas Dijkstra calculates the shortest path based on the minimum total weight in a network topology. This research employs a literature review supported by simulations conducted using [insert software name]. The results indicate that EIGRP outperforms in terms of convergence speed and adaptability to topology changes, while Dijkstra produces more optimal paths in terms of delay and hop count. The findings suggest that combining both approaches may enhance routing efficiency and provide a foundation for developing more adaptive and intelligent network systems.